3D virtual reconstruction and visualisation of the archaeological site Castellet de Bernabé (Llíria, Spain) - Cristina Portalés; Pau Alonso-Monasterio; María José Viñals (Virtual Archaeology Review)
3D virtual reconstruction of cultural heritage is a useful tool to reach many goals: the accurate documentation of our tangible cultural legacy, the determination of mechanical alteration on the assets, or the mere shape acquisition prior to restoration and/or reconstruction works, etc. Among these goals, when planning and managing tourism enhancement of heritage sites, it demands setting up specific instruments and tools to guarantee both, the site conservation and the visitors’ satisfaction. Archaeological sites are physical witnesses of the past and an open window to research works and scientific discoveries, but usually, the major structures do no exist nowadays, and the general public takes long time and many efforts to elaborate a mental reconstruction of the volumetry and appearance from these remains. This mental reconstruction is essential to build up a storyline that communicates efficiently the archaeological and historic knowledge and awares the public about its conservation. To develop this process of awareness about conservation, heritage interpretation starts with the mental inmersion of the visitors in the archaeological site, what 3D reconstruction definitely helps to achieve. Different technologies exist nowadays for the3D reconstruction of assets, but when dealing with archaeological sites, the data acquisition requires alternative approaches to be used, as most part of the assets do not exist nowadays. In this work, we will deal with the virtual reconstruction and visualisation of the archaeological site Castellet de Bernabé by following a mixed approach (surveying techniques and archaeological research). We further give a methodology to process and merge the real and virtual data in order to create augmented views of the site.